Perceived Social Effects of Tourism Development: A Case Study of Kinabalu National Park - Jaafar, Mastura; Ismail, Safura; Rasoolimanesh, Mostafa S. (Academy of Economic Studies, Romania, 2015)
We investigate the perceived social effects of tourism development on local communities from the perspective of local residents in selected locations near Kinabalu National Park. Local residents (n=378) were surveyed using a questionnaire and the collected data subjected to a series of descriptive analysis methods. Most respondents indicated that tourism, aside from being a stimulus for various cultural activities, had significantly increased their and other local people‟s pride in their national and local culture. Additionally, respondents indicated that community facilities had been improved as a result of tourism, and that their quality of life had also significantly improved. Paradoxically, the results indicated several negative effects, such as congestion and the exposure of anti-social behavior to the local community. However, the findings revealed that most local residents believed that the positive effects of tourism outweighed the negative. Obstacles to the sustainable Management of tourism in Kinabalu National Park must be overcome through the combined efforts of key stakeholders involved in tourism, including government and local authorities. The participation of the local community is an essential part of this bridging process because their involvement helps to protect and conserve the area as a tourist attraction. Moreover, participation can also help overcome negative social effects. Keywords: Positive perceived social effects, negative perceived social effect, tourism development, residents‟ perceptions, local community, sustainable tourism.